Induction of “Sakuntala” chrysanthemum bud using in-vitro culture - Tutut Wirawati; Ari Wijayani; Rina Srilestari (Jurnal Agrivet, 2012)
The research was to determine the best combination of Chrysanthemum explant and concentrations of BAP (6 - benzyl amino purine), the effect of the explant material and the effect concentrations of BAP (6 - benzyl amino purine) in vitro culture by Murashige and Skoog medium. The experimental methode was Completely Randomizes Design (CRD) which consisted of two factors. The first factor is the explant material, consisting of three standards are: P1 = node, P2 = shoots, P3 = leaf. The second factor is the concentration of BAP which consists of four levels, namely: B1 = 0.5 ppm, 1.0 ppm = B2, B3 = 1.5 ppm, B4 = 2.0 ppm. The results showed there were significant interaction on fresh weight, dry weight, number of shoots and length of shoots. The treatment combination between bud explants with BAP 0.5 ppm, showed the best results on fresh weight, number of shoots and long shoots. Use of explant shoots, can accelerate the current growth of shoots, expanding the number and length of root buds. The addition of plant growth regulators BAP 0.5 ppm in the tissue culture medium, can spur the rapid growth of shoots, root number and length of root best.Key words : in vitro, chrysanthemum, kinds of eksplant, the concentration of BAP